Beyond risk-taking: effects of psychological safety on cooperative goal interdependence and prosocial behavior - Leung, Kwok; Deng, Hong; Wang, Jie; Zhou, Fan (Sage, 2015)
In addition to risk-taking behavior, we propose that psychological safety also promotes prosocial behavior through cooperative goal interdependence. To differentiate these two types of effects, we contrasted the moderating effects of two interpersonal harmony motives. A survey in China supported the indirect effect of psychological safety on helping behavior through cooperative goal interdependence. This mediated relationship was moderated by harmony enhancement such that the mediated effect of psychological safety was weaker when harmony enhancement was high. Psychological safety was positively related to innovative behavior, and this relationship was moderated by disintegration avoidance such that it was weaker when disintegration avoidance was high. These results shed light on the different effects of psychological safety and their underlying mechanisms.